2020
DOI: 10.1136/gutjnl-2020-321411
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 in 79 patients with IBD in Italy: an IG-IBD study

Abstract: ObjectivesCOVID-19 has rapidly become a major health emergency worldwide. Patients with IBD are at increased risk of infection, especially when they have active disease and are taking immunosuppressive therapy. The characteristics and outcomes of COVID-19 in patients with IBD remain unclear.DesignThis Italian prospective observational cohort study enrolled consecutive patients with an established IBD diagnosis and confirmed COVID-19. Data regarding age, sex, IBD (type, treatments and clinical activity), other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
366
4
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(421 citation statements)
references
References 18 publications
31
366
4
13
Order By: Relevance
“…18 As of 16 June 2020, 57% of IBD patients taking oral or parenteral steroids needed hospitalization, with 19% experiencing unfavorable outcomes defined as intensive care unit admission, ventilator use, or death. 19 These findings were further supported by the results of the IG-IBD study, which reported a significant association between use of steroids and COVID-19-related pneumonia ( p = 0.05) and a trend towards increased mortality ( p = 0.064). 13 However, we cannot rule out that some confounding factors may have influenced these data.…”
Section: The Decaloguesupporting
confidence: 55%
See 1 more Smart Citation
“…18 As of 16 June 2020, 57% of IBD patients taking oral or parenteral steroids needed hospitalization, with 19% experiencing unfavorable outcomes defined as intensive care unit admission, ventilator use, or death. 19 These findings were further supported by the results of the IG-IBD study, which reported a significant association between use of steroids and COVID-19-related pneumonia ( p = 0.05) and a trend towards increased mortality ( p = 0.064). 13 However, we cannot rule out that some confounding factors may have influenced these data.…”
Section: The Decaloguesupporting
confidence: 55%
“…A retrospective study from the United States including a large cohort of IBD patients reported that the incidence rate of COVID-19 per 1000 IBD patients was of 0.61 in patients treated with anti-TNF-α and 1 in those not in treatment with anti-TNF-α ( p = 0.618). 16 Interestingly, a recent case report 17 and larger studies 18 , 19 hypothesized that anti-TNF-α antibodies could guarantee a milder course of COVID-19. In fact, in the SECURE-IBD database (>1500 patients enrolled), as of 16 June 2020, 16% of patients treated with anti-TNF-α agents required hospitalization, and only 2% experienced unfavorable outcomes, defined as intensive care unit admission, ventilator use, or death.…”
Section: The Decaloguementioning
confidence: 99%
“…There is no doubt that, in patients with IBD, the risk of infection or a severe course of disease is influenced by drug therapies ("therapy as a risk factor"). [58]. In view of these findings, adequate control of the underlying disease and compensation of nutritional deficiencies are therefore paramount.…”
Section: Recommendation 13mentioning
confidence: 99%
“…With regard to IBD-specific risk factors, it is speculated that patients on immunosuppressive agents, those with active IBD symptoms, malnutrition, and frequent visits to clinics or hospitals are at greater risk of acquiring SARS-CoV-2 infection [ 50 ]. In an Italian study of 79 IBD patients, the risk factors associated with COVID-19-related mortality included age >65 years (OR 19.6, 95%CI 2.95-130.6), Charlson comorbidity index >1 (OR 16.6, 95%CI 1.80-153.9), and active IBD (OR 8.5, 95%CI 1.26-56.56) [ 51 ]. Table 1 outlines the risk factors for COVID-19 infection and poor outcomes [ 2 - 4 , 7 , 13 , 51 ].…”
Section: Risk Factors For Sars-cov-2 Infection In Ibdmentioning
confidence: 99%